Accessions during the Year - Anonymus, A. (1952)
Bronze Pin-Head (from Luristan; 7th Century B. C.); Bronze Head of Pazuzu (from Nimrud; 8th Century B. C.); Bronze from Luristan (8th-6th Century B. C.); 1951.